Micro and Nano Systems Letters - Kim, Jongbaeg
Micro and Nano Systems Letters is an international open access journal published by SpringerOpen. The MNSL offers express online publication of short research papers containing the latest advances in micro and nano-scaled devices and systems. It also offers a rapid route for the international dissemination of high quality research findings from both the micro and nano communities. Manuscripts should report new and significant findings that represent recent advances and practical applications of micro and nano systems engineering. The journal’s specific areas include, but are not limited to: • Micro & Nano Fabrication Technologies • Packaging Technologies • Materials and Device Characterization • Mechanical Sensors and Systems • Physical (Optical, Magneto) Devices • RF MEMS • Bio and Chemical Sensors and Systems • Medical Microsystems • Micro & Nano Fluidic Components and Systems • Micro & Nano Actuators • Energy Harvesting and Power Systems • Nano-Electro-Mechanical Devices and Systems.